Sistem Pendukung Keputusan Seleksi Calon Putri Pariwisata Nias Barat Menerapkan Metode Weight Aggregated Sum Product Assesment (WASPAS) - Wiwien Ngesti Hia; Mesran; Fince Tinus Waruwu (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2022)
Princess tourism is one of the promotional media to introduce the culture of the region and the tourism potential that each region has. The tourism and culture office of West Nias regency held a selection to get the best daughter to become a tourism princess in accordance with the provisions. The process is still classified as manual making the selection process longer and less efficient. The assessment system using SPK is very helpful for judges in the selection process to get the best daughters from the many daughters listed. In this study, the authors used the Weight Aggregated Sum Product Assessment (WASPAS) method to assist a system that can assist judges in the selection process based on predetermined criteria. The application of Weight Aggregated Sum Product Assessment) (WASPAS) is expected to facilitate judges in the selection process that is in accordance with the criteria, faster and more efficient as expected.